Structure, Texture and Catalytic Properties of Pd/SiO Catalysts - S.A. El-Hakam; Awad I. Ahmed; S.M. Hassan; H.M. Farage (Adsorption Science & Technology)
The structural properties of Pd/silica catalysts have been investigated by means of DTA and X-ray techniques. The X-ray results indicate that Pd metal is the only phase formed. The textural properties were determined using low-temperature nitrogen adsorption. Surface areas were calculated and the dependence of the surface area on the metal content has been discussed. Pore structure analyses indicate the presence of both micro-and meso-pores. The dehydrogenation of cyclohexane was found to be affected by the metal content. The active site for the dehydrogenation process on Pd/silica catalysts consists of one Pd atom. The kinetics of the dehydrogenation exhibit a fractional order.